Training Of Trainer Pada Caregiver Tentang Personal Hygiene di Panti Werdha Marfati Tangerang - Safitri, Alfika; Jessica, Agnes; Azzahra Medi, Alsa; Aulia, Alvira; Almasyah, Ashila; Asih; Fatimatussa’diah; Amalia, Fazlatul; Husnaini; Wira, Iftitah (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Personal hygiene is an effort to maintain personal cleanliness and health. This includes various activities aimed at keeping the body and the surrounding environment clean and healthy. Personal hygiene includes personal hygiene, namely hair cleanliness, brushing teeth, wearing clean clothes, nail cleanliness, foot cleanliness and one of them is also diapers. Objective: The purpose of this activity is so that care givers can learn the theory and how to prevent the spread of disease and infection by maintaining body hygiene, one of which is the cleanliness of urinating and defecating with diapers. Method: This Training of Trainers is divided into 4 stages, namely, the preparation stage, providing Training of Trainers (TOT), implementing Training of Trainers (TOT) and final reporting. Result: Results after doing it presentation and demonstration of material regarding Personal Hygiene (Helps defecate and urinate by using diapers) obtained care giver knowledge (good), attitudes (good), and practices (Good). Conclusion: The results of the Training of Trainers health education activities on Personal Hygiene (Helping to Defecate and Urinate Using Diapers) at the Marfati Werdha Home in Tangerang City. The training of trainers can understand and demonstrate personal hygiene in the elderly. The Pre-Test and Post-Test questions are the benchmark for the success of participants in this activity. That most of the companions understand it.